Late-onset epilepsy predicts future stroke: a systematic review and meta-analysis. Issue 6 (27th May 2022) - Wall, Jasmine; Knight, Jo; Emsley, Hedley
Abstract : Late-onset epilepsy (LOE) is closely associated with cerebrovascular disease. LOE also appears to be a harbinger of dementia. We performed a systematic review of observational studies, clinical studies and radiological studies relating to LOE. We conducted a meta-analysis of 5 observational studies and have found that patients presenting with LOE experience an increased risk of subsequent stroke, weighted OR 3.88 (95% CI 2.76 - 5.46). Above the age of fifty, incidence of new onset epilepsy is approximately 400/100, 000 person years. Of these, 9.8–11.9% will have a stroke in the decade following epilepsy onset, translating to an incidence of «pre-stroke epilepsy» of 25–55/100, 000 person years. The additional studies demonstrated clinical and radiological evidence to support the premise that LOE is likely to reflect underly- ing cerebrovascular disease. Cerebrovascular risk factors convey increased risk of LOE, and LOE can act as a «harbinger» for stroke and dementia, with various proposed pathophysiological mechanisms. The onset of LOE may represent a potential point for intervention, with the aim of stroke prevention. Current data supports the need for prospective research in order to better understand the natural history of LOE, disease mechanisms and opportunities for intervention to reduce the apparent sequelae of stroke and dementia. jasminewall@googlemail.com